Heterophile antibody positive, acute cytomegaloviral infection in an immunocompetent pre-teen: An atypical presentation of an atypical infection. Issue 1 (January 2015) - Raja, Junaid; de Quesada, Gonzalo
Summary Mononucleosis and mononucleosis-like illnesses comprise a significant proportion of pediatric and adolescent infectious illnesses. By far, the most common cause of these illnesses is Epstein–Barr virus, which causes mononucleosis, and a distant second is cytomegalovirus, which is the most common cause of mononucleosis-like illnesses. This case provides an interesting juxtaposition of laboratory findings of an adolescent who was heterophile antibody positive but acute Epstein–Barr virus antigen–antibody negative. A subsequent immunologic assay resulted in a final diagnosis of an acute cytomegaloviral infection. This is, to our knowledge, the first such report in the literature.